Effect of thermal radiation on unsteady magneto-hybrid nanofluid flow in a π -shaped wavy cavity saturated porous medium - Rashad, A. M.; Kolsi, Lioua; Mansour, M. A.; Salah, T.; Mir, Ahmed; Armaghani, Taher; Alshammari, Badr M. (Frontiers in Chemistry, 2024)
The present investigation deals with the natural convection (NC) of Al 2 O 3 -Cu-water hybrid nanofluid (HNF) within a " "-shaped cavity under the influence of an externally applied magnetic field (MF). Also we studied the porous media with radiative effect as well as common heat transfer for better fitting to real industrial problems. The inverse U shapedcavity design includes upper walls that are partially heated and wavy right and left walls designed for cooling purposes, while the remaining walls are maintained as adiabatic. A FORTRAN home code using finite difference method-based approach is adopted to solve the governing equations. A verification is performed by comparing with previous numerical investigations to substantiate the precision of the established numerical model. The findings are expressed in term of stream function, isotherms, and local and averaged Nusselt number.It was found that by increasing amplitude (A), location of the heater (D), thermal radiation parameter (Rd) and wavelength (λ) about 140%, 94%, 775%, and 28% N uavg increases, respectively. In addition, by increasing Dimensionless of heat source/sink length (B), Ha, and heat generation/absorption coefficient (Q) about 20%, 1.1% and 28% N uavg decreases, respectively. Also, N uavg first decreases and then increases by increasing Ra.